2016
DOI: 10.1186/s12863-016-0454-6
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the genomic architecture of bull fertility in Holstein cattle

Abstract: BackgroundFertility is considered an important economic trait in dairy cattle. Most studies have investigated cow fertility while bull fertility has received much less consideration. The main objective of this study was to perform a comprehensive genomic analysis in order to unravel the genomic architecture underlying sire fertility in Holstein dairy cattle. The analysis included the application of alternative genome-wide association mapping approaches and the subsequent use of diverse gene set enrichment tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 61 publications
0
86
0
2
Order By: Relevance
“…Previous studies have successfully identified potential genes and pathways affecting service sire fertility in Holstein breed (e.g., Blaschek et al . ; Han & Peñagaricano ; Whiston et al . ; Nicolini et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have successfully identified potential genes and pathways affecting service sire fertility in Holstein breed (e.g., Blaschek et al . ; Han & Peñagaricano ; Whiston et al . ; Nicolini et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our group has been investigating potential genetic factors underlying the observed variation in SCR in dairy cattle. We have identified regions on BTA21 and BTA25 that explain a significant amount of additive genetic variance (Han & Peñagaricano ). In addition, we recently reported significant non‐additive effects on BTA8, BTA9, BTA13 and BTA17 (Nicolini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association testing between microarray-derived genotypes and semen characteristics uncovered quantitative trait loci (QTL) that are associated with male reproduction in cattle (e.g., [27][28][29][30][31][32][33]). These studies provided evidence that inherited differences in semen quality are amenable to genome-wide association testing.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called single step methods (i.e., Single Step GBLUP (SSGBLUP) and Single Step SNP-BLUP (SSSNP-BLUP)) project enotypes into phenotyped individuals, using pedigree relationships [1316]. These “single step methods” allow the estimation of breeding values and also marker effects [15,17,18], and the latter have been used for GWAS analysis [1921], typically by size of estimated marker effects or a similar measure such as the proportion of genetic variance explained by a marker or segment. A common pitfall of GWAS methods based on size of effects or variances explained is the lack of a formal framework for acceptance/rejection of hypothesis – in particular, there is no clearly defined statistic to be used for hypothesis testing, and there is no empirical statistical law or closed-form solution under the null hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…[22]. For instance, [19] studied “the 20 largest explanatory loci”, [20] studied “the 10 windows explaining the largest amount of genomic variance for gene annotation, gene network and pathway analyses” whereas [21] considered “1.5 Mb SNP windows that explained more than 0.50 % of the genetic variance”. Thus, there is no formal hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%